Sequence Determinants of TDP-43 Ribonucleoprotein Condensate Formation and Axonal Transport in Neurons - Vishal, Sonali S.; Wijegunawardana, Denethi; Salaikumaran, Muthu Raj; Gopal, Pallavi P. (Frontiers in Cell and Developmental Biology, 2022)
Mutations in TDP-43, a RNA-binding protein with multiple functions in RNA metabolism, cause amyotrophic lateral sclerosis (ALS), but it is uncertain how defects in RNA biology trigger motor neuron degeneration. TDP-43 is a major constituent of ribonucleoprotein (RNP) granules, phase separated biomolecular condensates that regulate RNA splicing, mRNA transport, and translation. ALS-associated TDP-43 mutations, most of which are found in the low complexity domain, promote aberrant liquid to solid phase transitions and impair the dynamic liquid-like properties and motility of RNP transport granules in neurons. Here, we perform a comparative analysis of ALS-linked mutations and TDP-43 variants in order to identify critical structural elements, aromatic and charged residues that are key determinants of TDP-43 RNP transport and condensate formation in neurons. We find that A315T and Q343R disease-linked mutations and substitutions of aromatic residues within the α-helical domain and LARKS, show the most severe defects in TDP-43 RNP granule transport and impair both anterograde and retrograde motility. F313L and F313-6L/Y substitutions of one or both phenylalanine residues in LARKS suggest the aromatic rings are important for TDP-43 RNP transport. Similarly, W334F/L substitutions of the tryptophan residue in the α-helical domain, impair TDP-43 RNP motility (W334L) or anterograde transport (W334F). We also show that R293A and R293K mutations, which disrupt the only RGG in the LCD, profoundly reduce long-range, directed transport and net velocity of TDP-43 RNP granules. In the disordered regions flanking the α-helical domain, we find that F283Y, F397Y or Y374F substitutions of conserved GF/G and SYS motifs, also impair anterograde and/or retrograde motility, possibly by altering hydrophobicity. Similarly, ALS-linked mutations in disordered regions distant from the α-helical domain also show anterograde transport deficits, consistent with previous findings, but these mutations are less severe than A315T and Q343R. Overall our findings demonstrate that the conserved α-helical domain, phenylalanine residues within LARKS and RGG motif are key determinants of TDP-43 RNP transport, suggesting they may mediate efficient recruitment of motors and adaptor proteins. These results offer a possible mechanism underlying ALS-linked TDP-43 defects in axonal transport and homeostasis.